Sydney - Womersley, Steve; Neustein, Rachel (DK eyewitness top 10 travel guides., 2015)
Provides background information on Sydney, Australia. Recommends the 10 best restaurants, bars, nightlife, neighborhoods, hotels, and local attractions.